Vanadium(IV) complexes inhibit adhesion, migration and colony formation of UMR106 osteosarcoma cells - Molinuevo, María Silvina (2008)
Vanadium is a trace element widely distributed in the environment. In vertebrates it is mainly stored in bone tissue. The unique cellular environment in the bone and the variety of interactions that mediate cancer metastasis determine that certain types of cancer, such as breast and prostate cancer, preferentially metastize in the skeleton. Since this effect usually signifies serious morbidity and grave prognosis there is an increasing interest in the development of new treatments for this pathology. The present work shows that vanadium complexes can inhibit some parameters related to cancer metastasis such as cell adhesion, migration and clonogenicity. We have also investigated the role of protein kinase A in these processes.